Notes on the Setaria palmifolia Group (Gramineae) in Malesia - L. G. Saw; T. Uji; J. F. Veldkamp (PTTI, 1997)
The Setaria plicata in the flora of Java is S. barbata. The true S. plicata has been found only once in Malesia (Celebes), and must be regarded as a variety of S. palmifolia. The new combination S. palmifolia var. blepharoneuron is proposed and lectotype of panicum recipiens var. spicatum-paniculatum is indicated.